2019
DOI: 10.1177/1747493019830589
|View full text |Cite
|
Sign up to set email alerts
|

Location-specific differences in hematoma volume predict outcomes in patients with spontaneous intracerebral hemorrhage

Abstract: Background and objective Functional outcome after spontaneous intracerebral hemorrhage (ICH) may vary depending on hematoma volume and location. We assessed the interaction between hematoma volume and location, and modified the original ICH score to include such an interaction. Methods Consecutive ICH patients were enrolled in the Intracerebral Hemorrhage Outcomes Project from 2009 to 2017. Inclusion criteria were age≥18 years, baseline modified Rankin Scale (mRS) score 0–2, neuroimaging, and follow-up. Functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 44 publications
2
21
1
Order By: Relevance
“…Consistent with previous studies [ 11 , 21 ], advanced age, GCS score, presence of IVH, and PLIC involvement were also associated with mRS > 3. In our study, 95.95% (403/420) of the patients were found with hypertension.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with previous studies [ 11 , 21 ], advanced age, GCS score, presence of IVH, and PLIC involvement were also associated with mRS > 3. In our study, 95.95% (403/420) of the patients were found with hypertension.…”
Section: Discussionsupporting
confidence: 91%
“…One study demonstrated that baseline hematoma size categories of <10 mL had the same ability to predict outcome regardless of the HE de nition [21]. Ironsideet al modi ed the original ICH score and the volume cutoff was less than 10 mL in the deep and brainstem location [8].Therefore, it is meaningful to discriminate hematomas with a benign clinical course from those with a malignant course so the effects of interventions could be improved. Our results showed that very small hematomas (<3 mL) had a higher rate of HE compared to those with a volume of 3-10 mL, but with a more benign outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Intracerebral hemorrhage (ICH) is the most devastating subtype of stroke with high morbidity and mortality [1]. Baseline hematoma volume is an independent predictor of hematoma expansion (HE) and poor outcome in patients with ICH [2,3].Although patients with smaller hematomas are more likely to have a benign clinical course [4,5], some studies reported that small hemorrhage in deep locations caused functional dependence or mortality, and the volume cutoff to predict poor outcome was less than the widely used of 30 mL [6][7][8]. In a prior study, small ICH was de ned as benign or malignant, and patients with the latter experienced HE and had worse outcomes [5].…”
Section: Introductionmentioning
confidence: 99%
“…9 Despite intraventricular clot resolution, acute CSF flow obstruction can progress into persistent hydrocephalus and may require the placement of a VP shunt for permanent CSF diversion. 10 Few studies have been performed about the progression from acute to chronic hydrocephalus and related factors. In this study, we sought to investigate early predictors of long-term shunt dependency in patients with ICH who had received EVD placement for emergency CSF diversion.…”
Section: Introductionmentioning
confidence: 99%